Leveraging Value Chain Analysis to Drive Growth in the Muslim Fashion Industry: A Small and Medium Enterprise Strategy Case Study - Silitonga, Roland Y.H.; Setiawati, Marla; Triutami, Eunike Novana; Indriati, Ellen (The Indonesian Institute of Science and Technology Research, 2023)
This article presents a comprehensive case study that utilises value chain analysis to analyse and develop strategies for small and medium enterprises (SMEs) operating in the Muslim fashion industry. The research addresses critical challenges facing SMEs in accessing the final market and proposes strategic solutions for all stakeholders involved in the value chain. The study adopts Kaplinsky's value chain analysis approach, complemented by quantitative tools such as SWOT and Diamond Competitiveness Analysis. The findings reveal that SMEs encounter four significant barriers to accessing the final market: economies, product characteristics, heavy promotion and advertising, and trading barriers. These barriers pose significant challenges due to internal limitations within the organisations. With these obstacles, a multifaceted strategy is proposed. The proposed plan includes the following key initiatives: (1) Segmentation of the target consumer base to optimise services, thus maximising penetration; (2) Strengthening collaborative partnerships between different actors within the value chain to enhance overall competitiveness; (3) Implementation of targeted promotion and communication programs to improve customer satisfaction and brand visibility; (4) Establishment of a comprehensive data recording system to streamline business processes and improve tactical decision-making; and (5) Investment in technological advancements within the production process to enhance product quality. By implementing these strategies, SMEs can effectively address the identified barriers and unlock their growth potential within the Muslim fashion industry. This case study contributes to the existing body of knowledge by providing practical insights and recommendations for SMEs operating in the Muslim fashion sector. The findings can guide policymakers, industry practitioners, and researchers in formulating effective strategies to foster growth and sustainability in this dynamic industry.